Synergistic effect of multimodal γ' precipitates tuned through Ti addition on phase stability and strength of Co-Ni based superalloy - Mazumder N.; Kumar D.; Singh M.P.; Makineni S.K.; Mukhopadhyay N.K.; Chattopadhyay K. (My University, 2025)
The paper explores the role of multimodal γ' distribution in a CoNi-based superalloy on their thermophysical and mechanical properties. Three categories of γ' size distribution as primary, secondary type-1, and secondary type-2 were obtained by varying Ti composition (2, 4, and 6 at.%) in a Co-30Ni-7Al-2Nb (at.%) alloy. The study reveals an anomaly in primary γ' solvus with an increase in Ti composition that influences the microstructure. The anomaly can be related to the interplay between Nb and Ti composition in the γ'. We report a direct correlation among the nature of γ' distribution, its composition, and the yield strength of the alloys at room and high temperatures. © 2022 Acta Materialia Inc.